Detection of FeChPV in a cat shelter outbreak of upper respiratory tract disease in China - Hao, Xiangqi; Li, Yanchao; Chen, Bo; Wang, Hanhong; Wang, Xinrui; Xiao, Xiangyu; Zhou, Pei; Li, Shoujun (Frontiers in Microbiology, 2022)
Feline parvovirus often causes a fatal infectious disease and has a serious impact on domestic cats and wild felines. Feline chaphamaparvovirus (FeChPV) is a novel type of feline parvovirus that has been successively identified in Canada, Italy and Turkey. The prevalence and pathogenicity of FeChPV in other regions is still unknown. In this study, we recorded the detection of FeChPV in a cat shelter in China. A high prevalence (81.08%, 30/37) of FeChPV was detected in cats with symptoms of upper respiratory tract disease (URTD) in this cat shelter. Multiple pathogen testing indicated high coinfection rates of 80% (24/30) with other common viruses in FeChPV-positive cats. Analyses of the necropsy and histopathological findings revealed severe lymphadenitis, encephalitis, and viral DNA in several tissues (including brain) of the deceased cat. Finally, we obtained nearly full-length genomes of four strains with 98.4~98.6% homology with previously reported genomes. Notably, VP1 proteins showed seven unique amino acid mutations, while NS1 proteins carried eight mutations. In the evolutionary tree based on VP1 and NS1, the sequences clustered in a large branch with Italian and Canadian FeChPV strains. Given the possible association of FeChPV with URTD, further studies are necessary to evaluate the pathogenicity and epidemiological characteristics of this novel feline pathogen.